Antecedents and consequences of brand love - Leskinen, Katariina (2021)
Brand love is a relatively new marketing related notion, that has proven to have several desirable consequences for brand managers. The conceptualization of the construct is still in its early stages, but the amount of brand love related studies has seen an increase during the las few decades. Today, the word “love” is often used to describe objects. However, when talking about objects or brands, the word might have a different meaning for consumers compared to situations when the word is used to describe relationships with other human beings. This study aimed to contribute to the already existing brand love research by examining potential antecedents and consequences of brand love, and creating a research model including constructs that were adopted from previous studies. The purposed antecedents for brand love included in this study were brand identification, brand trust and hedonic product value. The purposed consequences were brand commitment, active engagement and willingness to pay a price premium. Quantitative research method was used. The data collected was conducted by an online questionnaire, and a sample of 108 responses was received. IBM SPSS Statistics 24 was used at first to start the process of analysing the data. After that partial least squares structural equation modelling (PLS-SEM) in SmartPLS 3 was used to study the research model. Two of the six hypotheses set in the research model were supported. This was mainly due to high col-linearity between the original constructs. According to the present study, brand love has a significant relationship with brand commitment. Brand love was also found to impact willingness to pay a price premium. This study supports the previous knowledge and existing theories of brand love having several desirable consequences for brand managers. Both brand commitment and willingness to pay price premiums have been discovered to be consequences of brand love in previous studies, and this study supports these findings as well.